(untitled) - Berenson, Alex. (New York, 2014)
"A suspense novel featuring former CIA agent John Wells, by the author of THE SHADOW PATROL and THE NIGHT RANGER"--
Kirkus Reviews
Booklist
Library Journal
Publishers Weekly
Adult.
Adult.
Keywords: Intelligence officers; Fiction; Criminal investigation; Fiction; Spy stories